Hybridization Of Natural Fibre Polymer Composite - Harith, Ahmad Asri Abd (Universiti Sains Malaysia, 2021)
Synthetic fibers such as carbon, glass, and kevlar are used as reinforcements and are proven to be the best in respect to the properties, reinforcing ability and application. However, natural fibers such as coir, jute, sisal, flax, hemp, kenaf and more are nowadays widely used as reinforcements, as they are on par with the properties of synthetic fibers. Hence, this project focused on the hybridization of natural fibre and polymer composite. This project research is focus on evaluation the mechanical properties of the composite of hybridization of coir and epoxy. For research purposes, the composite sample is prepared using two different length of coir fibre. First sample is using natural length and second sample is using fibre that have been cut shortly. The experimental works including the treatment of the fibre which involving alkaline treatment and the fabrication of the composite which involving hand lay-up process following by vacuum bagging process. The treatment and fabrication process were same for both composite samples prepared. However, the initial plan is to implement nano particles such as Carbon Nanotubes and study its effected to mechanical properties of the composite. Unfortunately, due to pandemic my experimental work does not followed the initial planned as the access to lab is limited. The specimens were then having tensile test and flexural test to determine the tensile strength and flexural strength of the composite. As for the result, the length of the fibre sure affected the tensile modulus and flexural modulus of the coir/epoxy composite prepared. The chemical treatment on the coir fibre also shows improvement on the mechanical properties of the composite.